Prognostic Factors for Low Visual Acuity after Cataract Surgery with Vitreous Loss - Michael Mimouni; Michal Schaap-Fogler; Philip Polkinghorne; Gilad Rabina; Rita Ehrlich (Journal of Ophthalmology)
Purpose. The purpose of this study is to find prognostic factors associated with low visual acuity in patients experiencing vitreous loss during cataract surgery. Methods. A retrospective, noncomparative, interventional, case study of patients experiencing vitreous loss during cataract surgery. Data collected included demographics, best corrected visual acuity (BCVA), axial length (AL), presence of ocular comorbidity affecting central vision, timing of intraocular lens (IOL) implantation, position of the implanted lens, and the presence of corneal sutures. Low visual outcome was defined as BCVA < 20/40. Results. Overall, 179 patients (60.3% males) with a mean age of 73 ± 12 years and axial length of 23.5 ± 1.3 mm with a mean follow-up of 12 ± 13 months were included. In multivariable logistic regression analysis, low visual outcome was independently associated with persisting postoperative complications (OR 6.25, 95% CI 1.378–30.9), preexisting ocular comorbidities (OR 4.45, 95% CI 1.1–18.00), and secondary intraocular lens (IOL) implant (OR 10.36, 95% CI 1.8–60.00). Conversely, pars plana vitrectomy (PPV) for dislocated fragments of lens material, age > 70 years, gender, axial length, degree of surgeon, corneal suturing, and anterior chamber lens implantation were not found to have significant associations with low visual outcomes (P>0.05). Conclusions. Low visual outcome after vitreous loss during cataract surgery was associated with ocular comorbidities, secondary IOL implantation, development of cystoid macular edema, and additional surgical complications.